A long-life lithium-ion battery negative electrode material and preparation method thereof

By using carbon dioxide activated graphite and cobalt salt catalyst in the negative electrode material of lithium-ion battery, carbon nanotubes are grown and combined with fluorination treatment to form carbon fluorinated carbon, the problem of low structural stability and circulation performance of the material is solved, and more efficient Lithium ion transmission and cycling performance improves.

CN116253320BActive Publication Date: 2024-12-20INNER MONGOLIA XINYUAN GRAPHENE TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310241132.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2024-12-20
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have poor structural stability and low cycling performance during fast charging and circulation, which are mainly due to the irreversible capacity loss and structural damage caused by the transmission of lithium ions on the surface of the material.

Method used

Carbon nanotubes are grown by activated graphite and doped with cobalt salt catalyst, and fluorinated carbon carbon is formed by combining fluorination treatment to enhance the structural stability of the material and improve the cyclic performance of the material by doping lithium salt.

Benefits of technology

It improves the structural stability and cycling performance of the material, reduces irreversible capacity loss, improves the charging and discharging efficiency and dynamic performance of the material, and extends the life of the lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116253320B_ABST
    Figure CN116253320B_ABST
Patent Text Reader

Abstract

The present invention discloses a long-life lithium-ion battery negative electrode material and a preparation method thereof, and belongs to the technical field of lithium-ion battery material preparation. The preparation method of the long-life lithium-ion battery negative electrode material comprises the following steps: (1) adding graphite to a cobalt salt solution for immersion, then introducing carbon dioxide gas, and performing high-temperature activation to obtain modified graphite; (2) adding the modified graphite, asphalt, and lithium salt to an organic solvent, dispersing them evenly, and then performing vacuum immersion under heating conditions to obtain a graphite precursor material; (3) performing high-temperature fluorination treatment on the graphite precursor material to obtain the long-life lithium-ion battery negative electrode material. The long-life lithium-ion battery negative electrode material prepared by the present invention is applied to lithium-ion batteries, and has the advantages of excellent cycle performance and low expansion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery material preparation, and in particular to a long-life lithium ion battery negative electrode material and a preparation method thereof. Background Art

[0002] As the market's requirements for fast charging and cycle mileage of lithium-ion batteries increase, the negative electrode materials used in lithium-ion batteries are required to have high energy density while having excellent fast charging and power performance. The power-type artificial graphite currently used in the market is mainly composed of core graphite and soft carbon or hard carbon coated on the surface. During its charging and discharging process, lithium ions are mainly transmitted through the soft carbon or hard carbon on the surface of the material, and lithium ions are consumed during the cycle, resulting in reduced cycle performance. At the same time, the expansion of the material during the cycle causes poor structural stability, which further leads to reduced cycle performance. The measures to improve the material's cycle performance are mainly to reduce surface defects of the material, expand the material interlayer spacing, reduce structural damage during the material's charging and discharging process, and supplement the material with lithium to increase the transmission rate of lithium ions, thereby reducing irreversible capacity loss and improving cycle performance. How to achieve the above performance improvement has become a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0003] The purpose of the present invention is to provide a long-life lithium-ion battery negative electrode material and a preparation method thereof to solve the problems existing in the prior art. The present invention utilizes carbon dioxide to activate graphite and a cobalt salt catalyst doped therewith to grow carbon nanotubes between the materials, while expanding the graphite layer, doping lithium salts to improve the structural stability of the material, and fluorinating the surface of the graphite to form fluorinated carbon to improve the structural stability of the material and improve the cycle performance of the material.

[0004] To achieve the above object, the present invention provides the following solutions:

[0005] One of the technical solutions of the present invention: a method for preparing a negative electrode material for a long-life lithium-ion battery, comprising the following steps:

[0006] (1) adding graphite into a cobalt salt solution (catalyst) for immersion, then introducing carbon dioxide gas for high temperature activation to obtain modified graphite;

[0007] (2) adding the modified graphite, asphalt (softening point: 80-120° C.), and lithium salt into an organic solvent, dispersing them uniformly, and then vacuum immersing them under heating conditions to obtain a graphite precursor material;

[0008] (3) subjecting the graphite precursor material to a high-temperature fluorination treatment to obtain the long-life lithium-ion battery negative electrode material.

[0009] Furthermore, in step (1), the cobalt salt solution is a 0.1 mol / L cobalt chloride solution; and the immersion time is 0.5 to 2 hours.

[0010] Furthermore, in step (1), the flow rate of the carbon dioxide gas is 30 to 120 mL / min; the temperature of the high-temperature activation is 700 to 1000° C., and the time is 1 to 6 hours.

[0011] Furthermore, in step (2), the mass ratio of the modified graphite, asphalt, lithium salt and organic solvent is 100:(1-5):(1-5):(500-1000).

[0012] Furthermore, the lithium salt includes any one of lithium triethylborohydride, lithium trifluoromethanesulfonate, lithium acetate, lithium benzoate, lithium oxalate, lithium oxalate and lithium amide; and the organic solvent includes any one of cyclohexane, carbon tetrachloride, N-methylpyrrolidone and carbon disulfide.

[0013] Furthermore, in step (2), the heating temperature is 80 to 150° C.; the vacuum immersion pressure is -0.9 MPa, and the time is 12 to 36 hours.

[0014] Furthermore, in step (3), the fluorine source for the high-temperature fluorination treatment is a mixed gas of fluorine and argon, the heating rate is 1 to 10°C / min, the temperature is 700 to 1100°C, and the time is 1 to 6 hours.

[0015] Furthermore, the mixed gas of fluorine gas and argon gas is a mixed gas of fluorine gas and argon gas in a volume ratio of (1-5):10; and the flow rate of the mixed gas of fluorine gas and argon gas is 10-100 mL / min.

[0016] The second technical solution of the present invention: a long-life lithium-ion battery negative electrode material prepared by the above preparation method.

[0017] The third technical solution of the present invention: an application of the above-mentioned long-life lithium-ion battery negative electrode material in the preparation of lithium-ion batteries.

[0018] The present invention discloses the following technical effects:

[0019] (1) The present invention improves the structural stability of the material by infiltrating a catalyst (cobalt salt solution) between graphite layers and using it as a matrix to grow carbon nanotubes; and the present invention reduces irreversible capacity loss and improves cycle performance by doping with lithium salts.

[0020] (2) The present invention forms carbon fluoride on the surface of the material by fluorination treatment. The carbon fluoride has the characteristics of high compatibility with the electrolyte, which can reduce irreversible capacity loss and improve cycle performance.

[0021] (3) The present invention uses carbon dioxide to activate and expand the pores of graphite, which has the advantages of high efficiency, and the carbon dioxide molecules are small and can easily expand into the graphite interlayer with good uniformity. It can increase the interlayer spacing of the material while reducing expansion and improving the cycle performance.

[0022] (4) The present invention first uses carbon dioxide to expand the graphite layer to obtain modified graphite, and then uses low softening point (softening point: 80-120°C) asphalt and lithium salt to fill its pores, and through fluorination treatment, obtains a fluorinated carbon-coated graphite precursor material (graphite composite material). The carbon fluoride in the graphite composite material prepared by the present invention has good compatibility with the electrolyte and can reduce side reactions on the surface of the material; the lithium salt replenishes the lithium ions consumed during the charging and discharging process, which can reduce the irreversible capacity of the material and improve the cycle performance; at the same time, low softening point asphalt is used to fill the interlayer of graphite and fill it through carbonization to reduce side reactions, and the large interlayer spacing of graphite is used to improve the dynamic performance and reduce expansion. The graphite composite material prepared by the present invention is applied to lithium-ion batteries and has the advantages of excellent cycle performance and low expansion. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a SEM image of the graphite composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0026] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0030] The softening point of the asphalt used in the following examples and comparative examples of the present invention is 80-120°C.

[0031] Example 1

[0032] A method for preparing a negative electrode material for a long-life lithium-ion battery:

[0033] (1) 100 g of artificial graphite was added to 500 mL of a 0.1 mol / L cobalt chloride solution, fully immersed for 1 h, filtered, and dried at 80° C. for 24 h; then placed in a tubular furnace, heated to 900° C., and introduced with carbon dioxide gas (at a flow rate of 60 mL / min), and activated at high temperature for 3 h to obtain modified graphite.

[0034] (2) Add 100 g of modified graphite, 3 g of asphalt, and 3 g of lithium triethylborohydride to 800 g of cyclohexane, transfer to a ball mill and disperse evenly, then heat to 120°C at a pressure of -0.9 MPa, vacuum soak for 24 h, and vacuum dry at 80°C for 24 h to obtain a graphite precursor material.

[0035] (3) The graphite precursor material is transferred to a tubular furnace and a fluorine gas mixture is introduced (the volume ratio of fluorine gas to argon gas is 3:10, and the flow rate of the mixed gas is 50 mL / min). The temperature is then increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 h. Finally, the temperature is cooled to room temperature in an argon inert atmosphere to obtain a long-life lithium-ion battery negative electrode material (graphite composite material).

[0036] Example 2

[0037] A method for preparing a negative electrode material for a long-life lithium-ion battery:

[0038] (1) 100 g of artificial graphite was added to 500 mL of a 0.1 mol / L cobalt chloride solution, fully immersed for 0.5 h, filtered, and dried at 80° C. for 24 h; then placed in a tubular furnace, heated to 700° C., and introduced with carbon dioxide gas (at a flow rate of 30 mL / min), and activated at high temperature for 6 h to obtain modified graphite.

[0039] (2) Add 100 g of modified graphite, 1 g of asphalt, and 1 g of lithium trifluoromethanesulfonate to 500 g of carbon tetrachloride, transfer to a ball mill and disperse evenly, then heat to 80°C at a pressure of -0.9 MPa, vacuum soak for 36 h, and vacuum dry at 80°C for 24 h to obtain a graphite precursor material.

[0040] (3) The graphite precursor material is transferred to a tubular furnace and a fluorine gas mixture is introduced (the volume ratio of fluorine gas to argon gas is 1:10, and the flow rate of the mixed gas is 100 mL / min). The temperature is then increased to 700°C at a heating rate of 1°C / min and kept at this temperature for 6 h. Finally, the temperature is cooled to room temperature in an argon inert atmosphere to obtain a long-life lithium-ion battery negative electrode material (graphite composite material).

[0041] Example 3

[0042] A method for preparing a negative electrode material for a long-life lithium-ion battery:

[0043] (1) 100 g of artificial graphite was added to 500 mL of a 0.1 mol / L cobalt chloride solution, fully immersed for 2 h, filtered, and dried at 80° C. for 24 h; then placed in a tubular furnace, heated to 1000° C., and introduced with carbon dioxide gas (at a flow rate of 120 mL / min), and activated at high temperature for 1 h to obtain modified graphite.

[0044] (2) Add 100 g of modified graphite, 5 g of asphalt, and 5 g of lithium acetate to 1000 g of N-methylpyrrolidone, transfer to a ball mill and disperse evenly, then heat to 150°C at a pressure of -0.9 MPa, vacuum soak for 12 h, and vacuum dry at 80°C for 24 h to obtain a graphite precursor material.

[0045] (3) The graphite precursor material is transferred to a tubular furnace and a fluorine gas mixture is introduced (the volume ratio of fluorine gas to argon gas is 5:10, and the flow rate of the mixed gas is 10 mL / min). The temperature is then increased to 1100°C at a heating rate of 10°C / min and kept at that temperature for 1 h. Finally, the temperature is cooled to room temperature in an argon inert atmosphere to obtain a long-life lithium-ion battery negative electrode material (graphite composite material).

[0046] Comparative Example 1

[0047] Preparation of graphite composite materials:

[0048] (1) 100 g of artificial graphite, 3 g of asphalt, and 3 g of lithium triethylborohydride were added to 800 g of cyclohexane and transferred to a ball mill for uniform dispersion. The mixture was then heated to 120° C. at a pressure of −0.9 MPa, vacuum immersed for 24 h, and vacuum dried at 80° C. for 24 h to obtain a graphite precursor material.

[0049] (2) The graphite precursor material is transferred to a tubular furnace, argon gas is introduced (flow rate is 60 mL / min), and then the temperature is increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 h. Finally, the temperature is cooled to room temperature in an argon inert atmosphere to obtain a graphite composite material.

[0050] Comparative Example 2

[0051] Preparation of graphite composite materials:

[0052] (1) 100 g of artificial graphite was added to 500 mL of a 0.1 mol / L cobalt chloride solution, fully immersed for 1 h, filtered, and dried at 80° C. for 24 h; then placed in a tubular furnace, heated to 900° C., and introduced with carbon dioxide gas (at a flow rate of 60 mL / min), and activated at high temperature for 3 h to obtain modified graphite.

[0053] (2) Add 100 g of modified graphite and 3 g of asphalt to 800 g of cyclohexane, transfer to a ball mill and disperse evenly, then vacuum dry at 80° C. for 24 h to obtain a graphite precursor material.

[0054] (3) The graphite precursor material is transferred to a tubular furnace, and a fluorine gas mixture (the volume ratio of fluorine gas to argon gas is 3:10, and the flow rate of the mixed gas is 50 mL / min) is introduced, and then the temperature is increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 h. Finally, the temperature is cooled to room temperature in an argon inert atmosphere to obtain a graphite composite material.

[0055] Comparative Example 3

[0056] The same as Example 1, except that the carbon dioxide gas in step (1) is replaced by ammonia gas.

[0057] Comparative Example 4

[0058] The same as Example 1, except that step (1) is specifically as follows: 100 g of artificial graphite is placed in a tubular furnace, the temperature is raised to 900° C., and carbon dioxide gas (flow rate is 60 mL / min) is introduced, and high-temperature activation is performed for 3 h to obtain modified graphite.

[0059] Comparative Example 5

[0060] The same as Example 1, except that step (2) is specifically as follows: 100 g of modified graphite, 3 g of asphalt, and 3 g of lithium triethylborohydride are added to 800 g of cyclohexane, and the mixture is transferred to a ball mill for uniform dispersion, and then vacuum dried at 80° C. for 24 h to obtain a graphite precursor material.

[0061] Comparative Example 6

[0062] The same as Example 1, except that step (2) is specifically as follows: 100 g of modified graphite and 3 g of asphalt are added to 800 g of cyclohexane, and transferred to a ball mill for uniform dispersion, and then heated to 120°C under a pressure of -0.9 MPa, vacuum immersed for 24 h, and vacuum dried at 80°C for 24 h to obtain a graphite precursor material.

[0063] Effect Example 1

[0064] SEM Testing

[0065] The graphite composite material prepared in Example 1 of the present invention was subjected to SEM testing, and the results are shown in Figure 1 .

[0066] from Figure 1 It can be seen that the graphite composite material prepared in Example 1 of the present invention is in a granular state with a reasonable size distribution and a particle size between 3 and 10 μm.

[0067] Effect Example 2

[0068] Physical and chemical performance test and button battery test:

[0069] According to the national standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries", the material's interlayer spacing D002, specific surface area, tap density, particle size and particle size distribution are tested.

[0070] The graphite composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 6 were used as negative electrodes (formula: composite material C: CMC: SBR: SP: H 2 O=95:2.5:1.5:1:150), lithium sheet as counter electrode, LiPF electrolyte 6 / EC+DEC, the electrolyte solvent volume ratio EC:DEC=1:1, the diaphragm adopts a composite film of polyethylene PE, polypropylene PP and polyethylene propylene PEP, the button battery is assembled in an argon-filled glove box, the electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, the charge and discharge voltage range is controlled at 0.005-2.0V, the charge and discharge rate is 0.1C, and finally assembled into button batteries A1 (Example 1), A2 (Example 2), A3 (Example 3) and B1-B6 (Comparative Examples 1-6).

[0071] Table 1

[0072]

[0073]

[0074] Table 2

[0075]

[0076] It can be seen from Tables 1 to 2 that the button cells prepared using the graphite composite materials of Examples 1 to 3 have a large interlayer spacing and a higher first efficiency. The reason is that the particle size distribution of the graphite composite materials is narrow, the side reactions are fewer, and the first efficiency is higher. At the same time, the carbon dioxide modification is used to expand the interlayer spacing of the material, and the doped lithium salt reduces the irreversible capacity of the graphite composite materials, thereby improving the first efficiency and rate performance.

[0077] Effect Example 3

[0078] Soft pack battery test:

[0079] The graphite composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were mixed and coated to prepare negative electrode sheets, NCM523 ternary material was used as the positive electrode, the solvent was EC / DEC / PC (EC:DEC:PC=1:1:1) as the electrolyte, and the solute was LiPF 6 , Celgard 2400 membrane was used as the separator, and 5Ah soft-pack batteries C1 (Example 1), C2 (Example 2), C3 (Example 3) and D1-D6 (Comparative Examples 1-6) were prepared respectively.

[0080] Test the liquid absorption capacity of the negative electrode and the cycle performance of the battery (2.0C / 2.0C).

[0081] Liquid absorption capacity test:

[0082] Liquid absorption test: Use a 1mL burette and absorb 1mL of electrolyte, drip a drop on the surface of the electrode, and time it until the electrolyte is completely absorbed, and record the time t. The test results are shown in Table 3.

[0083] The cycle test method is: 2C / 2C, 2.8-4.2V, 25±3℃, 500 weeks; the test results are shown in Table 3.

[0084] Table 3

[0085]

[0086] It can be seen from Table 3 that the liquid absorption and retention capabilities of the negative electrode sheets prepared using the graphite composite materials of Examples 1 to 3 are significantly better than those of Comparative Examples 1 to 6. The reason is that the graphite composite materials prepared in Examples 1 to 3 have a high specific surface area, which can improve the liquid absorption capacity of the graphite composite materials; at the same time, the graphite composite materials prepared in Examples 1 to 3 are doped with carbon nanotubes, which can improve the structural stability of the material during the charge and discharge process, reduce expansion, and rely on the lithium salt doped therein to increase the insertion and extraction rate of lithium ions during the charge and discharge process, thereby improving the cycle performance.

[0087] Effect Example 4

[0088] Rate performance: Charge the soft pack battery to 100% SOC at a rate of 2C using constant current + constant voltage mode, and then calculate the constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity). See Table 4 for test results.

[0089] Table 4

[0090] Negative electrode materials used in batteries Fast charging performance (constant current ratio, %) Example 1 93.5 Example 2 92.5 Example 3 93.9 Comparative Example 1 90.6 Comparative Example 2 90.7 Comparative Example 3 88.8 Comparative Example 4 88.1 Comparative Example 5 90.6 Comparative Example 6 91.0

[0091] It can be seen from Table 4 that the rate performance (fast charging performance) of the battery prepared using the graphite composite materials of Examples 1 to 3 is better than that of Comparative Examples 1 to 6. The reason is that the graphite composite materials prepared in the examples have a large interlayer spacing, which can increase the insertion and extraction rate of lithium ions during the charging and discharging process of the material, thereby improving the rate performance of the material.

[0092] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a negative electrode material for a long-life lithium-ion battery, characterized in that: The following steps are involved: (1) adding graphite into a cobalt salt solution for immersion, then introducing carbon dioxide gas for high temperature activation to obtain modified graphite; (2) adding the modified graphite, asphalt and lithium salt into an organic solvent, dispersing them evenly, and then vacuum immersing them under heating conditions to obtain a graphite precursor material; (3) subjecting the graphite precursor material to a high-temperature fluorination treatment to obtain the long-life lithium-ion battery negative electrode material; In step (1), the cobalt salt solution is a 0.1 mol / L cobalt chloride solution; the immersion time is 0.5 to 2 hours; In step (2), the heating temperature is 80 to 150° C.; the vacuum immersion pressure is -0.9 MPa, and the time is 12 to 36 hours; In step (3), the fluorine source for the high-temperature fluorination treatment is a mixed gas of fluorine and argon, the heating rate is 1 to 10°C / min, the temperature is 700 to 1100°C, and the time is 1 to 6 hours; The mixed gas of fluorine gas and argon gas is a mixed gas of fluorine gas and argon gas in a volume ratio of (1-5):10; the flow rate of the mixed gas of fluorine gas and argon gas is 10-100 mL / min; In step (1), the flow rate of the carbon dioxide gas is 30 to 120 mL / min; the temperature of the high temperature activation is 700 to 1000° C., and the time is 1 to 6 hours; In step (2), the mass ratio of the modified graphite, asphalt, lithium salt and organic solvent is 100:(1-5):(1-5):(500-1000).

2. The preparation method according to claim 1, characterized in that: The lithium salt includes any one of lithium triethylborohydride, lithium trifluoromethanesulfonate, lithium acetate, lithium benzoate, lithium oxalate, lithium oxalate and lithium amide; the organic solvent includes any one of cyclohexane, carbon tetrachloride, N-methylpyrrolidone and carbon disulfide.

3. A long-life lithium-ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 2.

4. Use of the long-life lithium-ion battery negative electrode material according to claim 3 in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Lithium-ion battery anode materials and their preparation methods, lithium-ion batteries

    CN102299308A

  • Negative pole material for lithium ion power and energy storage battery, as well as preparation method and battery thereof

    CN103943860A

  • High-capacity silicon-based anode material for lithium ion battery and preparation method thereof, and lithium ion battery

    CN105576209A

  • Lithium ion battery negative electrode material with high coulombic efficiency and long cycle life

    CN109616637A

  • Modified graphite negative electrode material, preparation method thereof and battery containing modified graphite negative electrode material

    CN111276674A